Complex prosthetic treatment of a patient with chromium and nickel allergy - József Saláta; Péter Hermann; Emese Ábrám (Hungarian Dental Association, 2023)
Introduction: Nowadays, the number of patients suffering from allergic diseases is constantly increasing. Intraoral symptoms and complaints can be caused by dental materials, such as metals (most often nickel and palladium metal alloys) and polymers. In case of metal allergy, the use of traditional dental alloys containing the given material is contraindicated, but full-ceramic systems or titanium frameworks can be suitable alternatives. Case report: 46-year-old female patient showed up at Semmelweis University Department of Prosthodontics in 2019 with the purpose of replacing her missing teeth. The patient's allergy to eugenol, chromium and nickel was confirmed by an epicutaneous test. Following the current professional recommendations regarding the use of alternative materials, porcelain fused to zirconia crowns and composite fused to titanium fixed partial dentures were planned on the upper jaw. On the lower jaw, a complex denture was planned with a fixed part of a composite fused to titanium splint, and a removable part with dentomucosal support, precision attachments and titanium baseplate. The prosthetic phase was preceded by professional oral hygiene and conservative dental treatments. Summary: Due to high frequency of allergies, dentists should be aware that patients may be hypersensitive to certain dental materials in the everyday dental care. Although the treatment of these patients requires prudence, long-term success can be achieved by using alternative substances in appropriate indications.